Effectiveness and Side Effect Incidence in a Real-World Digital Weight-Loss Service Using Compounded Semaglutide: A Retrospective Comparative Study - Louis Talay; Matt Vickers (Obesities)
Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) were originally developed in the late 1980s as a class of antidiabetic medication. However, research over the past decade has found them to be a safe and effective weight-loss agent, which has led to the approval of GLP-1 RAs such as Semaglutide as a supplement to lifestyle obesity interventions in multiple countries. When Semaglutide has become commercially unavailable, digital weight-loss services (DWLSs) have prescribed a compounded form of the medication—a practice in which health professionals formulate a replica of the commercial medication to serve ongoing patient needs. Although compounding has been relatively common over the past century, prominent medical bodies have argued that compounding a relatively novel medication such as Semaglutide represents a major safety risk. This study retrospectively compared the weight and side effect outcomes of patients from a large Australian DWLS whose lifestyle coaching was supplemented with either compounded or pure Semaglutide (both groups following the same titration schedule). All data were extracted from the service’s central data repository. To be included in the weight loss analysis, patients needed to have received a minimum of four monthly medication orders between June 2023 and May 2024 and have submitted weight data between 90 and 150 days after the arrival of their first order. All patients who received at least one medication order within the same period were included in the side effect analysis. The mean four-month weight loss percentage was statistically lower in the compounded Semaglutide group (N = 923, M = 9.11, SD = ±5.76) compared to those in the pure Semaglutide group (n = 1858, M = 9.87, SD = ±6.46), t (2032) = −3.15, p = 0.0017. A statistically lower proportion of patients in the compounded Semaglutide group (71.61%) reported at least one side effect than patients in the pure Semaglutide group (77.40%) during the study period, X2 (1, N = 7683) = 32.32, p < 0.001. When side effects were disaggregated into severity categories, a statistical difference was only observed in mild side effects, X2 (1, N = 7683) = 59.16, p < 0.001. A significantly higher rate of patients from the pure Semaglutide group achieved the ten (50.54% vs. 44.64%), X2 (1, N = 7683) = 10.34, p < 0.001, and fifteen (21.42% vs. 12.78%), X2 (1, N = 7683) = 30.43, p < 0.001, percent weight loss thresholds than patients from the compounded Semaglutide group. The findings indicate that compounded Semaglutide can be used as a component of tightly controlled DWLSs with slightly less effectiveness but with slightly lower side effect incidence when compared to pure Semaglutide.